Conceptualization of the process and instrumental mechanisms of public administration in political science (Journal of Philosophy Culture and Political Science, 2020)
Public administration is studied as a process of formation, implementation and evaluation of public policies in the article. Public policy is seen as the result of a policy cycle. The scientific fields of the policy process analysis are determined. The purpose of the article is to discuss the instrumental mechanisms of public administration based on the conceptualization of the public policy cycle stages.The article addressed the following questions: on the relationship between the models of “policy stages” and “policy streams” with instrumental mechanisms of public administration; about application of the specific instruments / public administration tools in different political systems; about applicability of the external experience in the selection of public administration instruments; instrumental technologiesfor ensuring political stability, taking into account the assessment of the effectiveness of the public policy implementation.Methodology used in the article: deductive methods to gain general knowledge about procedural nature of public administration which were transformed into understanding of the policy implementation tools in the specific conditions, comparative analysis, observation and case studies methods were also used. The main results of the research: the classical model of “stages of public policy” is reduced to threestages: I) the agenda setting and public policy formulation; II) political decisions implementation; III) monitoring and evaluation of the implementation effectiveness. These three stages correlate with the political flows concept (problem stream, policy stream, politics stream). Instrumental mechanisms link policy formulation and policy implementation. Various classifications of the public policy instrumentsare presented. Types of public policy according to the T. Lowe’ classification (distributive, redistributive, regulatory, constituent types) are considered in connection with the dominant policy instruments. The scientific significance of the article consists in the increasing of knowledge about the processes of public administration. The practical significance is determined by the possibilities of applied scientificknowledge about the instruments of public administration.Key words: public administration, public policy, public policy instruments, policy cycle stages, policy streams, political science.